Improving Students’ Skills through the Production of Aromatherapy Candles Using a Combination of Cinnamon and Citronella Essential Oils - Noverda Ayuchecaria; Defilia Anogra Riani; Muhammad Priyadi; Thathit Suprayogi; Franz June Navirius; Nathanael Neda Galeno; Jessica Alexandra Roselia; Anggraeni Putri Esterlita (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2026)
Aromatherapy candles are candles made by mixing a base material, such as solid paraffin, with essential oils derived from certain plants. Training activities aimed at increasing knowledge in developing new products are still rarely conducted. This situation also occurs at SMA Negeri 2 Palangka Raya, where there is a lack of practical skills training programs that utilize local potential, as well as limited entrepreneurship development among students. This community service activity was conducted in October 2025 and aimed to provide training in making aromatherapy candles to students of SMA Negeri 2 Palangka Raya. This program employed the Participatory Action Research (PAR) method and focused on producing aromatherapy candles using a combination of cinnamon and citronella essential oils. The main participants were 45 tenth-grade students. The improvement in students’ skills was measured using pre-tests and post-tests, along with questionnaires regarding the aromatherapy candle-making training. The results showed that 53.33% of participants were interested in the skills to be acquired, 55.56% rated the implementation of the activity as very good, and 51.11% considered the theme of the activity to be very beneficial. Evaluation results indicated that 81.2% of participants demonstrated excellent knowledge in the candle-making process. The pre-test and post-test results also showed an improvement in scores after the training was conducted. In conclusion, the aromatherapy candle-making training using a combination of cinnamon and citronella essential oils at SMA Negeri 2 Palangka Raya was successfully implemented and achieved its intended objectives. This was evidenced by the high enthusiasm of participants and the improvement in their knowledge and skills after participating in the activity.